Starting school – parental perspectives in the United Arab Emirates in the first year. Issue 7 (3rd October 2022) - Takriti, Rachel; Atkinson, Susan; Alhosani, Najwa; Schofield, Lindsay; Elhoweris, Hala
ABSTRACT: Having a successful start to school as a young child has long been recognised as an important factor in ensuring a successful future educational career, associated with more positive social and academic outcomes. The current paper examines the expectations of parents for their children's first transition into school in early years and their actual lived experience of this. A repeated measures mixed methods approach utilising questionnaires and interviews was used to investigate this. Data were collected from two groups of parents, UAE nationals and British expats who had enrolled at least one child in a British curriculum private school in the city of Al Ain, UAE. Questionnaire data were collected at three different time points: beginning of the year, mid-way through the year, and end of the year. Significant differences were obtained relating to nationality and time on parental expectations. Thematic analysis was used to discover themes relating to parental expectations and experiences and two main themes emerged: 'Positive Experiences' and 'Adapting to Change'. Results are discussed through a phenomenological ecological systems perspective.